1962
DOI: 10.1161/01.res.10.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Arteriosclerosis in the Dog After Localized Aortic X-lrradiation

Abstract: Localized segments of the abdominal aortas of 18 dogs were irradiated with 50-kv. x-rays in doses ranging from 1,500 to 5,500 r (at the ventral surface of the aorta), and were examined histologically at intervals ranging from 2 to 48 weeks after irradiation. Arteriosclerosis developed at the irradiated sites and was significantly more severe than that which occurred in nonirradiated control sites in the abdominal aorta. There was evidence that severity of arteriosclerosis increased with time following irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Both survivor groups, those who received lower doses (1,800–3,000 cGy) and those who received higher doses (>3,000 cGy) of radiation, had significantly higher IMT and more plaque deposits than controls. While animal studies have demonstrated a dose response relationship between radiation and vascular injury [28], findings from adult cancer studies have been inconsistent [26,29]. As a result of these inconclusive findings, current recommendations for ultrasound screening of adult patients treated with neck irradiation are not based on radiation exposure, that is, dose [30].…”
Section: Discussionmentioning
confidence: 99%
“…Both survivor groups, those who received lower doses (1,800–3,000 cGy) and those who received higher doses (>3,000 cGy) of radiation, had significantly higher IMT and more plaque deposits than controls. While animal studies have demonstrated a dose response relationship between radiation and vascular injury [28], findings from adult cancer studies have been inconsistent [26,29]. As a result of these inconclusive findings, current recommendations for ultrasound screening of adult patients treated with neck irradiation are not based on radiation exposure, that is, dose [30].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is a well-known cause of vascular disease especially when vessels are exposed to radiation doses ranging from 25 to 40 Gy. 17 In our patient, the aortic pseudoaneurysm developed in a region that received a total radiation dose of 53.2 Gy (Figures 3 and 4 B). The metallic stent irradiated that could result in an overdose of 14% to 21% at a depth of 0.5 mm in the esophageal wall.…”
Section: Discussionmentioning
confidence: 60%
“…26 Radiation-induced or accelerated atherosclerotic changes in the carotid arteries have been well documented. [10][11][12][13][14][15][16][17] Arterial stenosis was localised to the common carotid artery in our study, and there was no increased incidence of intracranial arterial stenosis. This may be explained by the fact that the intracranial arteries are not directly within the centre of radiation port, and there is bone surrounding the vessels, thus they are not exposed to the same radiation dosage as the extracranial arteries.…”
Section: Discussionmentioning
confidence: 69%
“…Radiation-induced injury either causing or accelerating atherosclerotic changes in the carotid arteries has been well-documented in both experimental animal and human subjects. [8][9][10][11][12][13][14][15][16][17] Thus the possibility of post-irradiation intracranial arterial stenosis due to atherosclerosis is a particular concern. Intracranial atherosclerotic stenosis is a significant risk factor for stroke and is postulated to cause approximately 15% of all ischaemic events.…”
Section: Introductionmentioning
confidence: 99%